Lymphadenectomy for high-grade endometrial cancer: Does it impact lymph node recurrence?. Issue 5 (May 2022) - Swift, B.E.; Philp, L.; Atenafu, E.G.; Malkani, N.; Gien, L.T.; Bernardini, M.Q.
Abstract: Introduction: The diagnostic role of lymph node (LN) assessment is established in endometrial cancer. Our study assesses whether surgical removal of metastatic LNs has oncologic benefit in high-grade endometrial cancer. Materials and methods: High-grade endometrial cancer cases (2000–2010) were collected from two tertiary cancer centres. In patients with at least one positive LN, recurrence free survival (RFS) was compared by the number of LNs removed. Factors predicting nodal recurrence (NR) were explored. Univariate statistical analyses by log rank test and multivariable cox proportional hazards model were performed using SAS version 9.4. Results: Of 570 patients identified, 334 patients underwent staging lymphadenectomy, 74 (22.2%) patients had at least one positive LN. The median RFS with at least one positive lymph node was 87.1 months (95% CI ≥ 14.3) when greater than 15 LNs were removed, compared to 16.9 months (95% CI, 13.6–35.6) and 17.3 months (95% CI, 8.5–39.8) when 5–15 and less than 5 LNs were removed, respectively (p = 0.02). In the cohort of 570 patients, there were 167 disease recurrences with location described on imaging, 98 (58.7%) had a NR and 69 (41.3%) recurred at other sites. Multivariable modeling identified that only positive LNs at surgical staging predicted NR (HR 3.8, 95% CI 1.4–10.2). Conclusion: In high-grade endometrial cancer, positive LNs predict NR, and RFS is longer with a more extensive LN dissection in women with positive LNs. Future prospective studies should evaluate the oncologic benefit of surgical removal of metastatic LNs in high-grade endometrial cancer. Highlights: Positive LNs at surgical staging predict nodal recurrence. RFS longer with positive LNs when more extensive LN dissection performed. Surgical debulking positive LNs in high-risk endometrial ca may have oncologic role.